2017
DOI: 10.1038/ncomms15201
|View full text |Cite
|
Sign up to set email alerts
|

miR-29b contributes to multiple types of muscle atrophy

Abstract: A number of microRNAs (miRNAs, miRs) have been shown to play a role in skeletal muscle atrophy, but their role is not completely understood. Here we show that miR-29b promotes skeletal muscle atrophy in response to different atrophic stimuli in cells and in mouse models. miR-29b promotes atrophy of myotubes differentiated from C2C12 or primary myoblasts, and conversely, its inhibition attenuates atrophy induced by dexamethasone (Dex), TNF-α and H2O2 treatment. Targeting of IGF-1 and PI3K(p85α) by miR-29b is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
187
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 184 publications
(220 citation statements)
references
References 50 publications
16
187
0
1
Order By: Relevance
“…For example, miR-29 was decreased after acute myocardial infarction, which targets a cadre of mRNAs encoding proteins involved in fibrosis to promote the fibrotic response [5]. This was confirmed in another report in which miR-29b was shown to target insulin-like growth factor 1 and phosphatidylinositol 3-kinase and contribute to muscle atrophy [6]. Microarray profiling also showed alterations in genes related to ion channels by comparing DCM patients with controls: sodium voltage-gated channel beta subunit 2 was increased, while potassium voltage-gated channel subfamily J member 5/8, chloride intracellular channel 2/3, and calcium voltage-gated channel auxiliary subunit B2/A1C were decreased [7].…”
Section: Introductionsupporting
confidence: 60%
“…For example, miR-29 was decreased after acute myocardial infarction, which targets a cadre of mRNAs encoding proteins involved in fibrosis to promote the fibrotic response [5]. This was confirmed in another report in which miR-29b was shown to target insulin-like growth factor 1 and phosphatidylinositol 3-kinase and contribute to muscle atrophy [6]. Microarray profiling also showed alterations in genes related to ion channels by comparing DCM patients with controls: sodium voltage-gated channel beta subunit 2 was increased, while potassium voltage-gated channel subfamily J member 5/8, chloride intracellular channel 2/3, and calcium voltage-gated channel auxiliary subunit B2/A1C were decreased [7].…”
Section: Introductionsupporting
confidence: 60%
“…We performed a GO-term enrichment analysis of miR-29 targets with 8-mer seed matches and found that about half of the top pathways were related to ECM structure or insulin signaling, consistent with miR-29’s previously described roles in liver, cornea, muscle, and heart (Supplementary Fig. 2c) 21,22,23,24 . A closer examination of individual miR-29 targets, ranked by peak height, reveals that 4 of the top 10 genes have been previously validated in other cell types (Fig.…”
Section: Figsupporting
confidence: 81%
“…MiR-29b is the one that results in multiple types of muscle atrophy. Our research can further be applied to miR-29b (Li, et al, 2017). Furthermore, in the current models, we focus on the direct regulation between each miRNA and its target mRNA/protein, in the future, we will also take indirect regulation into consideration.…”
Section: Discussionmentioning
confidence: 99%